Physiotherapy’s Impact on an Athlete’s Physical and Mental Well-being: A Review - Apoorv Garg; Anil Kumar Garg; Jatinder Kaur (International Journal of Orthopedic Nursing and Practices, 2024)
Physiotherapists are essential in helping athletes with physical and psychological issues connected to their activity. Effective treatment and the formulation of athletes' expectations regarding the restoration of health issues require a solid interaction between the physiotherapist and the athlete. Thus, when designing a rehabilitation program, it is imperative to take the expectations of the athletes with the specific problem into consideration. Since the dawn of civilization, physiotherapy methods have been used as a therapeutic modality in all cultures, and their application in athletic contexts is well-established. Nonetheless, there is a dearth of empirical data about the physiological, psychological, and therapeutic benefits of widely applied physical therapy methods. This study examines both the most recent literature on the application of physiotherapy to athletes and the earlier and contemporary research on the subject. There was conflicting information on the best method and duration of application, and there was little consensus in English sources regarding the effectiveness of physical therapy. Clearly, further research is needed to determine the function of physiotherapy, a time-consuming approach used by physiotherapists, in order to settle certain controversial concerns surrounding this treatment modality and to support its usage.
Keywords: Sports; athletes; mental and physical health; physiotherapy